Pelatihan Pembuatan Nata de Coco Bagi Peserta Didik SMPN 13 Makassar - Sitti Saenab; Widya Astuti; Putri Diana Lisdayanti; Iqra Ramadani; Nur Rajemi Hasan (JKM: Jurnal Kemitraan Masyarakat, 2024)
This training aims to increase the knowledge and skills of participants in making nata de coco and open their insights about the application of conventional biotechnology in everyday life. This training was held at UPT SPF SMP Negeri 13 Makassar involving 15 students as participants. This training goes through the stages of 1) preparation 2) implementation; providing knowledge through lecture, question and answer, and discussion methods; practice making Nata de Coco. 3) Evaluation. This training utilizes conventional biotechnology principles, namely fermentation using the microorganism Acetobacter xylinum to convert sugar in cellulose media that forms the nata layer. The trainees were very enthusiastic about the training and successfully made Nata de Coco products. Nata de Coco produced by participants varied in thickness, color, aroma, and texture, most participants succeeded in producing Nata de Coco with good quality.